Silicoflagellates and ebridians from ODP Leg 138 holes - Kevin McCartney; J H Churchill; Linda Woestendiek (PANGAEA, 1995)
The biostratigraphic distribution and abundance of middle Miocene to Pleistocene silicoflagellates is documented from Ocean Drilling Program (ODP) Leg 138 Holes 844B, 847B, 848B, 849B, 850B, 85 IB, 852B, and 854B from the eastern Equatorial Pacific Ocean. The silicoflagellates were generally abundant and well preserved and frequently exhibited an unusually large range of variation. The upper Miocene of near-equatorial sites includes an assemblage of Bachmannocena diodon nodosa, which includes a bridge across the width of the basal ring. Stratigraphically below this, at sites within 5° of the equator is a lengthy interval of specimens of Distephanus speculum tenuis, which have a fragile apical structure. Both the intervals of Bachmannocena diodon nodosa plexus and Distephanus speculum tenuis are biostratigraphically useful within 5° of the equator, but are less useful beyond that. An unusual range of variation also is observed for Dictyocha in the Pliocene sediments at about the point where D. perlaevis and D. messanensis appear in the geologic record. This variation may be explained by hybridization between diverging species.
Supplement to: McCartney, K et al. (1995): Silicoflagellates and ebridians from Leg 138, eastern equatorial Pacific. In: Pisias, NG; Mayer, LA; Janecek, TR; Palmer-Julson, A; van Andel, TH (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 138, 129-162, https://doi.org/10.2973/odp.proc.sr.138.108.1995